A study on managing budgeting in the Immigration Department of Malaysia / Fatin Fatiqah Rosslan - Rosslan, Fatin Fatiqah (Faculty of Business and Management, 2010)
This study is about managing budget in the Immigration Department of Malaysia. Immigration Department of Malaysia is one of the government departments under the Ministry of Home Affairs (MOHA). Budgeting is an essential element of the financial planning, control, and evaluation processes of governments. Every governmental unit should prepare a comprehensive budget covering all governmental, proprietary, and fiduciary funds for each annual (or, in some states, biennial) fiscal period. Issue arises when the Director of Finance Division of Immigration Department of Malaysia, Puan Salma binti Sulaiman declared that budget applied for the year 2010 was decreased by the Ministry of Finance. Thus, this department should take the effective actions in managing their budget. Some objectives are derived from this study such as to know how to minimize budget expenditures, to know the types of expenditures incurred and to identify any actions to be taken by this department in managing their budget. In this study also used primary and secondary data. By analyzing company practices, information in terms of types of budgeting system, the departmental process budget, the types of policies and the types of expenditures implemented or practiced in this department can be used in completing this study.